Depot Buprenorphine Injection In The Management Of Opioid Use Disorder: From Development To Implementation - Ling W; Shoptaw S; Goodman-Meza D (Substance Abuse and Rehabilitation, 2019)
Walter Ling,1 Steve Shoptaw,1 David Goodman-Meza2 1UCLA Department of Family Medicine, Center for Behavioral and Addiction Medicine, Los Angeles, CA, USA; 2UCLA Department of Medicine, Division of Infectious Diseases, Los Angeles, CA, USACorrespondence: Walter Ling Email lwalter@ucla.eduAbstract: Buprenorphine has pharmacologic advantages over methadone, especially buprenorphine’s better safety profile. The true significance of buprenorphine’s introduction lies in returning the care of those suffering from opioid use disorder (OUD) to the hands of the physician. The clinical success of buprenorphine has been meager, in part because most physicians have not been exposed to treating these patients. For physicians inclined to treat OUD, the barriers to buprenorphine’s implementation have been onerous and largely counter to the norms of medical practice. Some notable concerns pertain to buprenorphine’s clinical pharmacology like street diversion, unintended use and accidental poisoning. Recently, injectable buprenorphine preparations have been introduced to mitigate these latter shortcomings. Yet, the injectable preparations’ clinical and commercial success has fallen far short of expectation. Here, we review the clinical pharmacology of these products and their expected clinical advantages for the manufacturers, clinicians, policy makers and patients, and offer our perspective, as clinicians and researchers, on how things can improve. Questions remain whether clinicians are willing to overcome barriers to treat OUD using these medications.Keywords: opioid use disorder, injectable buprenorphine, treatment barriers, stakeholders